Dispositional and contextual factors predicting smuggling behaviour among smugglers in border areas in Nigeria (2012)
Smuggling is one of the major factors undermining the economy of Nigeria. This behaviour is aided partly by the multi-border nature of the country with multiple entry and exit points (legal and illegal). The country shares land borders with Cameroon, Benin Republic, Republic of Togo, Chad and marine border with Equitorial Guinea. In a bid to stem the tide of smuggling, successive governments in Nigeria have put up a number of measures and legislation in addition to empowering the Nigeria Custom Service, yet the phenomenon has continued unabated. This study therefore, investigated some dispositional factors (openness to experience, agreeableness, neuroticism, conscientiousness, extraversion, locus of control, risk taking propensity and contextual factors (economic factors, family influence and peer influence) predicting smuggling behaviour. Two hundred smugglers were sampled in a cross-sectional survey using the snowball sampling technique in two selected border towns in Ogun State, Nigeria. Participants' age ranged from 20 - 60 years with a mean age of 37.13 and standard deviation of 8.43. Of the sample, 188 were males while 12 were females. Data was collected using a structured questionnaire comprising of 8 sections. Findings showed that all the independent variables jointly predicted smuggling behaviour (R = .80; R1= .63; p < .05. Meanwhile, openness to experience, agreeableness, conscientiousness, did not independently predict smuggling behaviour while extraversion and neuroticism did. It is thus recommended that government starts public awareness and re-orientation programmes aimed at bringing about attitudinal change beginning from elementary schools in order to shape the emerging personalities positively.